Targeting the α7 nicotinic acetylcholine receptor–A novel road towards the future treatment of skin diseases. Issue 9 (9th September 2020) - Stegemann, Agatha; Böhm, Markus
Abstract: Nicotinic acetylcholine receptors (nAChRs) are members of the superfamily of neurotransmitter‐gated ion channels. The natural ligand for nAChRs is the endogenous neurotransmitter acetylcholine. Among the nAChRs is the α7nAChR. It is not only expressed by neural tissues but also in the skin. A number of different resident cutaneous cell types including epidermal keratinocytes, sebocytes and dermal fibroblasts express functional α7nAChR. Moreover, cells of the immune system such as lymphocytes, macrophages and monocytes, playing an important role in skin homeostasis, also express α7nAChR. Translational research focusing on the exploitation of the α7nAChR in dermatology has revealed that this neuroendocrine receptor could be promising target for the treatment of inflammatory skin diseases. For example, α7nAChR agonists can counteract transforming growth factor‐β1‐mediated responses in dermal fibroblasts, key effector cells in scleroderma. In accordance with this α7nAChR, agonists are effective in both inflammation and non‐inflammation‐driven models of experimentally induced skin fibrosis. Moreover, α7nAChR agonists can modulate expression of proinflammatory cytokines in epidermal keratinocytes that are crucially involved in the pathogenesis of psoriasis and other inflammatory skin diseases. Finally, the capability of α7nAChR agonists to suppress ultraviolet light A/B‐induced responses, for example production of proinflammatory cytokines and oxidative stress, the latter crucially involved in dermal photoageing, points to a potential of such agents in the prevention of extrinsic skin ageing. Therefore, emphasis on translational research targeting the α7nAChR in skin may lead to the development of new treatment and prevention modalities against fibrosclerotic skin diseases, psoriasis vulgaris, atopic dermatitis, acne, photodermatoses and extrinsic skin ageing.